2010
DOI: 10.1103/physrevb.81.056101
|View full text |Cite
|
Sign up to set email alerts
|

Reply to “Comment on ‘Pb1xCaxTiO3solid solution (et al.

Abstract: Chandra ͓Phys. Rev. B 77, 017101 ͑2008͔͒ disagrees with the coexistence of a pseudocubic structure with a long-range tendency for cubic symmetry and tetragonal in a short-range order for the Pb 1−x Ca x TiO 3 ͑PCT͒ system obtained by the polymeric precursor method ͑PPM͒, as proposed in our original paper ͓Phys. Rev. B 75, 144111 ͑2007͔. However, we did not show the Rietveld results for the samples in this paper. The Rietveld refinement results shown clearly the coexistence of the tetragonal-cubic phases for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…According to Chandra et al [2,3], X-ray diffraction measurements showed an orthorhombic symmetry with Pbnm space group when x ≥ 0.42. On the other hand, Lázaro et al showed a tendency for the coexistence of cubic and tetragonal symmetries in which the weight percentage of tetragonal and cubic structure for Pb 0.50 Ca 0.50 TiO 3 was equal to 54.81% and 45.19%, respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Chandra et al [2,3], X-ray diffraction measurements showed an orthorhombic symmetry with Pbnm space group when x ≥ 0.42. On the other hand, Lázaro et al showed a tendency for the coexistence of cubic and tetragonal symmetries in which the weight percentage of tetragonal and cubic structure for Pb 0.50 Ca 0.50 TiO 3 was equal to 54.81% and 45.19%, respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the decreasing of Curie temperature, the addition of Ca 2+ ions to PbTiO 3 compound causes a structural phase transition and the appearance of a relaxor behavior. Although there are controversies about the crystalline symmetry in high Ca content samples [2][3][4][5]8]. According to Chandra et al [2,3], X-ray diffraction measurements showed an orthorhombic symmetry with Pbnm space group when x ≥ 0.42.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations